A Bilingual Epithalamium of Eighteenth-Century Lithuania: The Occasional Publication Dedicated to Karol Stanisław Radziwiłł and Teresa Karolina Rzewuska - Vaškelienė, Asta (Senoji Lietuvos literatūra, 2020)
The article presents, for the first time, a bilingual occasional publication, Celsissimo principi ac domino Carolo [...] Radivilio palatino Vilnensi fundatori suo munificentissimo. Et Teressiae illustrissimi comitis Venceslai Rzewuski [...] filiae quo die connubii faedus sanciunt. Societas Jesu provinciae Masoviae carmen geniale persolvit, Nesvisii: Typis Ducalibus Colleg. Soc. Jesu, dedicated to the wedding of Karol Stanisław Radziwiłł, known as Panie Kochanku (‘Dear Lord’), and Teresa Karolina Rzewuska, which took place in 1764. It was written in the name of the Jesuit Province of Masovia and printed in the printing house of Nesvizh in 1763 or 1764. This small book was printed in the quarto format and consists of two epithalamia in verse written in Latin and Polish. According to Karol Estreicher, both poems were authored by Jesuit Antoni Bartoszewicz, a professor in rhetoric. The Latin epithalamium is dedicated to both newlyweds, while the Polish epithalamium is dedicated only to the bride. The Latin epithalamium consists of two parts: ‘The Omen of Hymenaeus’ (Omen Hymenis) and ‘The Applause of Hymenaeus’ (Plausus Hymenaei). ‘The Omen of Hymenaeus’ is set in elegiac couplets and has 92 lines. ‘The Applause of Hymenaeus’ has 142 lines and its versification is heterogeneous: its beginning, the middle part, and the end are in hexameter interspersed with a few fragments in stressed versification imitating the classical metre. Compared to the Latin poem, the Polish poem is short (only 48 lines), set in the Polish alexandrine, which was popular at the time and with a rhythm resembling the classical hexameter. The phenomenon of bilingualism in Lithuanian occasional literature existed as long as the tradition of occasional works itself and was characteristic not only of epithalamia, but also of works of other genres. In epithalamia, it manifested itself in a specific form of linguistic attribution: the work in Latin would be dedicated to the groom or both newlyweds, and the work in Polish to the bride, who most likely did not know Latin. Such epithalamia were noticeably increasing in Lithuanian occasional literature of the eighteenth century. On the other hand, the factor of knowing the language should not be exaggerated as a separate literary greeting written in the recipient’s mother tongue was a sign of respect. ‘The Omen of Hymenaeus’, the first part of the Latin work, serves the function of a concise introduction and a lead-in to the situation. This section tells that the action takes place in the castle of Pidhirtsi, which is surrounded by a leafy forest. It also reflects the political realities of the time: an unhappy Poland, weeping for its rulers, Augustus III (died on 5 October 1763) and his wife Maria Józefa (died in 1757). What most links this section with the genre of the epithalamium is the intention of the work itself and the image of the wedding god Hymenaeus weaving modest wreaths of yellow roses in the shade (luteolis serta pudica rosis) are. The second part, ‘The Applause of Hymenaeus’, can be regarded as an exceptional example of wedding poetry in eighteenth-century occasional literature. Firstly, it is one of the few epithalamia in verse. Secondly, it contains an eighteenth-century invocation to Hymenaeus, or a refrain, which is almost unheard of in the eighteenth century and which is used in Catullus’ Poem 61. Thirdly, the poet’s use of canonical imagery clearly points to the influence of the classical tradition: the poem invokes the patronesses of fertility Latona and Juno, and the Pidhirtsian matchmaker (Pronuba Podhorcae), Charites, Aphrodite with her son Eros, Hymenaeus, and others are among its characters. Images typical of the classical tradition include the bed of the engaged couple strewn with hyacinth petals (sponsorum tori) and the motif of the flames of the newlyweds’ unfolding love (flammae novi conjugum amoris). An important feature of the epithalamium of the modern period is full equality of the groom and the bride: they are equal in birth, beauty, fame, respect shown them by others, and wealth. It is interesting to note that in paying homage to the genre, the wedding is first shown in the classical worldview and then in the Christian manner. In the latter, the poet replaces the invocation to Hymenaeus by an appeal to the Creator of heaven and earth (Tu caeli terraque Sator!) and revisits the country’s losses mentioned in the first part. Both the classical and the Christian episodes of this part close with the traditional motif of the epithalamium – a wish for heirs worthy of the couple. The ‘personal’ poem in Polish, dedicated to the bride, does not have any strong poetic links with the classical genre of the epithalamium. It is a panegyric in which the bride’s appearance, traits of her character, and her noble birth are praised through the lips of Nesvizh rejoicing at the forthcoming wedding. Although printed with the Latin epithalamium, this poem is essentially an occasional work in its own right. The analysis revealed the reception and adaptation of the tradition of the Roman genre in eighteenth-century Latin epithalamic poetry of Lithuania. The canonical system of images and classical stylistic ornamentation are overlaid with descriptions of specific places, details of the biography of the dedicatee, and the political realities of the region. The work is characterised by the harmony of the classical and Christian worldviews, the incorporation of mournful interludes, and the localisation of classical images (the Pidhirtsi matchmaker, the Pidhirtsi Hymenaeus). In the bilingual edition, the Polish poem is far removed from the canon of the classical epithalamium. Its affinity with wedding poetry is most evident in the bride’s encomium, which, among other things, reveals specific details of her biography. We do not find a description of the wedding feast itself or the gifts in the epithalamium of modern times. This also applies to the poems analysed, but it should be noted that they, and especially the poem in Latin, capture well the bustle of the forthcoming joyous celebration. The poem in Polish provides information about the decoration of the festivities: the triumphal arches being erected, the fireworks, and the slogans welcoming the wedding party.